2022
DOI: 10.1155/2022/1289445
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Analysis of an Individualized EMT-Related Gene Signature for the Prognosis of Breast Cancer in Female Patients

Abstract: Background. The current high mortality rate of female breast cancer (BC) patients emphasizes the necessity of identifying powerful and reliable prognostic signatures in BC patients. Epithelial-mesenchymal transition (EMT) was reported to be associated with the development of BC. The purpose of this study was to identify prognostic biomarkers that predict overall survival (OS) in female BC patients by integrating data from TCGA database. Method. We first downloaded the dataset in TCGA and identified gene signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…It is known that EMT is a cellular process which has been associated with a variety of tumor functions, including tumor initiation, tumor stemness, tumor cell migration, and drug resistance [ 17 ]. TNBC is one of the most studied malignant tumors, and a growing body of research has revealed that it is closely associated with EMT.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that EMT is a cellular process which has been associated with a variety of tumor functions, including tumor initiation, tumor stemness, tumor cell migration, and drug resistance [ 17 ]. TNBC is one of the most studied malignant tumors, and a growing body of research has revealed that it is closely associated with EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on univariate Cox analysis, we identified survival-associated genes from the most important module and established a risk signature consisting of six genes (LRP8, RNASE2, CLIP4, HAS2, SLC22A11, and KCTD12) using LASSO-Cox regression with the glmnet R package (version 4.1–8) and survival R package (version 3.5–7). After constructing the risk score, we employed Cox regression models, including univariate and multivariate Cox proportional hazards regression models, to investigate the effect of various factors, including the risk score, on survival time ( Xue et al, 2022 ). The TCGA samples were divided into a training set and a test set to validate our model, and with reference to the median score, we classified the KIRC patients into a low-risk group and a high-risk group.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the mechanisms involved in EMT are increasingly being studied. Several studies highlight new insights into EMT/MET processes, especially relate genetic signature [ 18 ], epigenetic alterations implication [ 19 , 20 ], structural alterations of the extracellular matrix (ECM) [ 20 ] as well as the interplay between immune system [ 21 , 22 ] and metabolic reprogramming (MR) [ 22 , 23 ], and how these factors affect the tumor growth and progression to metastasis of TNBC.…”
Section: Introductionmentioning
confidence: 99%